PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING STARTS WITH A QUESTION TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 BAYANG TAHUN PELAJARAN 2013/2014 - Susanti, Susi; Rismen, Sefna; Febriana, Rina (Pendidikan Matematika, 2013)
The background of this research is motivated by the shy students comprehension of mathematical concept class VIII SMPN 1 Bayang academic year 2013/2014. This study aims to determine whether students math concept comprehension by applying Active Learning types of Learning Starts With a Question better than student math concept comprehension with conventional learning. This type of research is experimental with the population of grade VIII SMPN1 Bayang academic year 2013/2014. Technique of random sampling, with VIII.1 as experimental class and VIII.3 as control class . Instrument used in this study is a test of Â math concept comprehension in the form of essays with a reliability test R11 = 0,75 , data analysis technique used is the one party t test with the help of software MINITAB. Based on the analysis of data obtained by the average post-test experimental class students is 76.26 higher than the control class it is 63.65 and the classes is normally distributed samples at significance level (Î±) = 0,05. From the results obtained hypothesis test p-value = 0,005 , then the hypothesis in this study received , so it can be concluded that the students math concept comprehension by learning the type of Active Learning types of Learning Starts With a Question better than the students math concept comprehension with conventional learning in class VIII SMPN1 Bayang academic year 2013/2014.